Remuneration Model and Delegation Leadership Impact on Job Satisfaction: Literature Review Study - Josua Panatap Soehaditama; Ari Sulistyowati; Rachmat Pramukty; Primadi Candra Susanto; Aswanti Setyawati (Green Publisher, 2024)
This article discusses the influence of remuneration and delegated leadership on employee job satisfaction. In today's competitive era, job satisfaction is a key factor influencing employee productivity and retention. This research uses a quantitative approach with a survey of employees in various industrial sectors to explore the relationship between financial rewards, recognition, and the leadership methods applied. The research results show that fair and competitive remuneration contributes significantly to job satisfaction, while effective delegation leadership increases employee autonomy and engagement. These findings indicate that the combination of adequate rewards and an empowering leadership approach can create a more satisfying work environment, which in turn improves organizational performance. This article suggests companies to integrate fair remuneration practices and development of delegation leadership skills in human resource management strategies to achieve higher job satisfaction.